Ameliorating efficacy of spermidine and kinetin for rhizospheric chromium and lead- indices for physiological studies of Mash [Vigna Mungo (L.) Hepper] - Yasin, Ghulam; Noman, Ali (Journal of Pure and Applied Agriculture, 2023)
Heavy metals toxicities have adverse effects on plant physiology while plant growth regulators improve the physiological phenomena of plants. An experiment was conducted to find out the ameliorative effects of spermidine and kinetin for toxicity of rhizospheric chromium (Cr) and lead (Pb) on four varieties of Mash bean [Vigna mungo (L.) Hepper]. Four varieties i.e., MASH 80, MASH 88, MASH 97 and MASH ES-1 were grown in pots with four replicates of each. Pots were arranged with complete randomization. After fifteen days of germination, the lead (Pb) was added @ 20 mg/kg and 40 mg/kg soil, while chromium (Cr) was supplied @ 30 mg/kg and 60 mg/kg soil in the form of PbCl2 and CrCl3 solutions. Spermidine @ 1.0 mM and Kinetin @ 100 mM were foliarly sprayed separately twice at age of 15 and 30 days of plants. Physiological parameters like nitrate reductase activity, photosynthetic rate, transpiration rate, substomatal CO2 concentration, stomatal conductance, water use efficiency were determined at the age of physiological maturity. Among the major significant findings, it was noted that the photosynthetic rate was increased by both spermidine and kinetin application. The maximum value (8.79) for photosynthetic rate was revealed under exogenous foliar spray of spermidine among the hormones. Transpiration rate was increased by kinetin. Substomatal CO2 concentration was decreased by both hormones. Kinetin increased stomatal conductance and decreased water use efficiency. The maximum value (169.40) for substomatal CO2 concentration was obtained by kinetin. The maximum value (1.08) for stomatal conductance was observed by foliar spray of kinetin among the hormones. Spermidine increased water use efficiency and nitrate reductase activity. The maximum value (7.78) for water use efficiency was recorded by spermidine. Conclusively, it was evident from the results that toxic effects of heavy metals were ameliorated by plant growth regulators and these findings can be helpful in ameliorating the metal toxicity effects in future. © 2021 Department of Agricultural Sciences, AIOU